2009
DOI: 10.1099/ijs.0.007179-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces baliensis sp. nov., isolated from Balinese soil

Abstract: The taxonomic positions of actinomycete strains T and ID03-0825, isolated from soil on the Indonesian island of Bali, were examined using a polyphasic taxonomic approach. The morphological and chemotaxonomic characteristics of these organisms are typical of the genus Streptomyces. Phylogenetic analyses performed using almost-complete 16S rRNA gene sequences demonstrated that the strains were closely related to Streptomyces glauciniger and Streptomyces lilacinus. However, DNA-DNA hybridization and phenotypic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Fortunately, Indonesia is also rich in terrestrial microbes, particularly in actinomycetes. Several scientists have reported that actinomycetes isolated from Indonesian soils and leaf-litters represent new species and demonstrate genus diversity (for example, Otoguro et al 2009, 2011; Lisdiyanti et al 2010; Yamamura et al 2010). Extensive exploration of industrially useful enzymes has been conducted from these actinomycetes, such as inulin fructotransferase (Pudjiraharti et al 2011, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, Indonesia is also rich in terrestrial microbes, particularly in actinomycetes. Several scientists have reported that actinomycetes isolated from Indonesian soils and leaf-litters represent new species and demonstrate genus diversity (for example, Otoguro et al 2009, 2011; Lisdiyanti et al 2010; Yamamura et al 2010). Extensive exploration of industrially useful enzymes has been conducted from these actinomycetes, such as inulin fructotransferase (Pudjiraharti et al 2011, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All Streptomyces species have LL-diaminopimelic acid in the cell wall peptidoglycan (Otoguro et al 2009) but no characteristic sugars (wall chemotype I sensu Lechevalier and Lechevalier 1970). Members of the genus Streptomyces have a wide range of metabolic abilities and produce a number of enzymes and chemical compounds, including antibiotics, enzyme inhibitors, vitamins, antitumour agents and antifungal compounds (McCarthy and Williams 1992;Chun et al 1997;Kim and Hwang 2003;Bérdy 2005;Kim et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Streptomyces are Gram-positive bacteria that form extensively branched substrate and aerial mycelia, which can differentiate into spore chains for reproduction. The genus serves as a reservoir for a broad range of secondary metabolites [16,17], notably antibiotics, and species manage to survive in diverse environments, including ditch sediment [18], soil [19][20][21], lake [22] and hot water spring [23].…”
Section: Introductionmentioning
confidence: 99%